2012
DOI: 10.5489/cuaj.11161
|View full text |Cite
|
Sign up to set email alerts
|

Challenging the 10-year rule: The accuracy of patient life expectancy predictions by physicians in relation to prostate cancer management

Abstract: : Physicians do poorly at predicting life expectancy and tend to underestimate how long patients have left to live. This overall inaccuracy raises the question of whether physicians should refine screening and treatment criteria, find a better proxy or dispose of the criteria altogether.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
2
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 22 publications
0
14
2
3
Order By: Relevance
“…Leung and colleagues highlights yet another concern central to this conversation -the ability of clinicians to effectively identify men with sufficient life expectancy to benefit from the early diagnosis and intervention. 2 These results are perhaps not surprising in the face of previous reports suggesting that almost 10% of men treated in Ontario die of other causes within 10 years of definitive treatment of their disease. 3 The "layers of uncertainty" 4 that have resulted from this knowledge gap have complicated our ability to communicate and support our patients, especially those who are considering PSA testing or contemplating their preferred management for localized disease.…”
contrasting
confidence: 51%
“…Leung and colleagues highlights yet another concern central to this conversation -the ability of clinicians to effectively identify men with sufficient life expectancy to benefit from the early diagnosis and intervention. 2 These results are perhaps not surprising in the face of previous reports suggesting that almost 10% of men treated in Ontario die of other causes within 10 years of definitive treatment of their disease. 3 The "layers of uncertainty" 4 that have resulted from this knowledge gap have complicated our ability to communicate and support our patients, especially those who are considering PSA testing or contemplating their preferred management for localized disease.…”
contrasting
confidence: 51%
“…2,3 Although competing risks of mortality for men with localized prostate cancer are well recognized, 38,39 clinicians often poorly estimate life expectancy. 6,7 Adjusting life tables for comorbidity scores obtained from the SEER-Medicare database improves non-cancer survival estimates for recently diagnosed cancer patients. 16 Comorbidity-adjusted life expectancy varied considerably among Medicare beneficiaries, suggesting the importance of considering comorbidity in tailoring treatment decisions in older patients.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 One explanation is that physicians have difficulty accurately estimating the effect of competing mortality risks on life expectancy. [6][7][8] Several comorbidity measures have been developed based on claims data, 9,10 but these tools are most widely used in health services research. 11 The American Urological Association (AUA) treatment guideline suggests using life-table analyses to inform treatment decisions, 2 but these population-based estimates exclude health status and may not be readily applicable to predicting the life expectancy of an individual patient.…”
mentioning
confidence: 99%
“…[1][2][3][4] Although their conclusion stated that respondents tend to underestimate LE, interestingly, their results also showed that for patients with short LE (<10 years), respondents were more likely to overestimate LE rather than underestimate. For example, for the single patient with LE <5 years, virtually all respondents overestimated his LE.…”
mentioning
confidence: 71%